1999
DOI: 10.1103/physrevlett.82.4707
|View full text |Cite
|
Sign up to set email alerts
|

First Order Transitions and Multicritical Points in Weak Itinerant Ferromagnets

Abstract: It is shown that the phase transition in low-T c clean itinerant ferromagnets is generically of first order, due to correlation effects that lead to a nonanalytic term in the free energy. A tricritical point separates the line of first order transitions from Heisenberg critical behavior at higher temperatures. Sufficiently strong quenched disorder suppresses the first order transition via the appearance of a critical end point. A semiquantitative discussion is given in terms of recent experiments on MnSi, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
318
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 259 publications
(347 citation statements)
references
References 13 publications
24
318
4
Order By: Relevance
“…The extreme chemical disorder in these alloys is an essential component of the physics, suppressing a first order ferromagnetic transition that invariably occurs in many other potential ferromagnetic quantum critical point (FQCP) systems. 9 In carefully prepared single crystals with electropolished surfaces and minimum mechanical damage, we find that the BKV theory 17,18 of metallic ferromagnetic QCPs provides an excellent description of all of our data. The approximate temperature-magnetic field phase diagram that describes the boundary between the quantum critical and the Fermi liquid regions is also determined for the NiCoCr 0.8 composition from magnetization data.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The extreme chemical disorder in these alloys is an essential component of the physics, suppressing a first order ferromagnetic transition that invariably occurs in many other potential ferromagnetic quantum critical point (FQCP) systems. 9 In carefully prepared single crystals with electropolished surfaces and minimum mechanical damage, we find that the BKV theory 17,18 of metallic ferromagnetic QCPs provides an excellent description of all of our data. The approximate temperature-magnetic field phase diagram that describes the boundary between the quantum critical and the Fermi liquid regions is also determined for the NiCoCr 0.8 composition from magnetization data.…”
Section: Introductionmentioning
confidence: 93%
“…The subscript T for γ and β indicate the temperature dependence of the relevant variables when the composition x has been tuned to its critical value (x cr ≈ 0.8) where the transition temperature is zero. This is also the notation used in the BKV theory 17,18 . These experimental values for γ T , δ, and β T are also the values predicted from BKV theory in the "dirty" or high-disordered limit.…”
Section: As Is Illustrated Inmentioning
confidence: 99%
“…Although the paramagnetic to ferromagnetic transition is often considered as a prototype of a second order phase transition, it has been proposed that a generic feature of itinerant ferromagnets is that the transition becomes first order when it is suppressed towards zero temperature [214]. This implies that the phase diagrams of the uranium-based ferromagnetic superconductors described below may not, strictly speaking, contain QCPs.…”
Section: Ferromagnetic Superconductorsmentioning
confidence: 92%
“…The SCR theory has so far been applied to second order transitions, and no specific calculations have been performed for free energies of first order transitions based on the SCR theory. Belitz et al 54,55 reported that a first order transition can be expected as generic phenomena due to the logarithmic term in the free energy in ferromagnets with itinerant electrons. The experimental results in MnSi and (Sr,Ca)RuO 3 are consistent with this theory, although they do not necessarily provide definitive proof.…”
Section: B Behavior Indicating First-order Transitionsmentioning
confidence: 99%